Extraction–Pyrolytic Method for TiO2 Polymorphs Production - Serga, Vera; Burve, Regina; Krumina, Aija; Romanova, Marina; Kotomin, Eugene A.; Popov, Anatoli I. (MDPI, 2021)
The unique properties and numerous applications of nanocrystalline titanium dioxide (TiO2) are stimulating research on improving the existing and developing new titanium dioxide synthesis methods. In this work, we demonstrate for the first time the possibilities of the extraction–pyrolytic method (EPM) for the production of nanocrystalline TiO2 powders. A titanium-containing precursor (extract) was prepared by liquid–liquid extraction using valeric acid C4H9COOH without diluent as an extractant. Simultaneous thermogravimetric analysis and differential scanning calorimetry (TGA–DSC), as well as the Fourier-transform infrared (FTIR) spectroscopy were used to determine the temperature conditions to fabricate TiO2 powders free of organic impurities. The produced materials were also characterized by X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM). The results showed the possibility of the fabrication of storage-stable liquid titanium (IV)-containing precursor, which provided nanocrystalline TiO2 powders. It was established that the EPM permits the production of both monophase (anatase polymorph or rutile polymorph) and biphase (mixed anatase–rutile polymorphs), impurity-free nanocrystalline TiO2 powders. For comparison, TiO2 powders were also produced by the precipitation method. The results presented in this study could serve as a solid basis for further developing the EPM for the cheap and simple production of nanocrystalline TiO2-based materials in the form of doped nanocrystalline powders, thin films, and composite materials. This work is licensed under a CC BY 4.0 license.
The authors thank V. Kuzovkov, A. Lushchik and M. Lushchik for many useful discussions. The research was (partly) performed in the Institute of Solid State Physics, University of Latvia ISSP UL. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2 under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; titanium dioxide; anatase; rutile; polymorphs; extraction–pyrolytic method